Proteome of synaptosome-associated proteins in spinal cord dorsal horn after peripheral nerve injury - Singh, O.; Yaster, M.; Xu, J.; Guan, Y.; Guan, X.; Dharmarajan, Arunasalam; Raja, S.; Zeitlin, P.; Tao, Y. (Wiley - VCH Verlag GmbH & Co. KGaA, 2009)
Peripheral nerve injury may lead to neuroadaptive changes of cellular signals in spinal cord that are thought to contribute to central mechanisms underlying neuropathic pain. Here we used a 2-DE-based proteomic technique to determine the global expression changes of synaptosome-associated proteins in spinal cord dorsal horn after unilateral fifth spinal nerve injury (SNI). The fifth lumbar dorsal horns ipsilateral to SNI or sham surgery were harvested on day 14 post-surgery, and the total soluble and synaptosomal fractions were isolated. The proteins derived from the synaptosomal fraction were resolved by 2-DE. We identified 27 proteins that displayed different expression levels after SNI, including proteins involved in transmission and modulation of noxious information, cellular metabolism, membrane receptor trafficking, oxidative stress, apoptosis, and degeneration. Six of the 27 proteins were chosen randomly and further validated in the synaptosomal fraction by Western blot analysis. Unexpectedly, Western blot analysis showed that only one protein in the total soluble fraction exhibited a significant expression change after SNI. The data indicate that peripheral nerve injury changes not only protein expression but also protein subcellular distribution in dorsal horn cells. These changes might participate in the central mechanism that underlies the maintenance of neuropathic pain. © 2009 Wiley-VCH Verlag GmbH & Co. KGaA.